Epoxide Functional Temperature‐Sensitive Semi‐IPN Hydrogel Microspheres for Isolating Inorganic Nanoparticles. Issue 1 (4th January 2016) - Ahmad, H.; Alam, M. M.; Rahman, M. A.; Minami, H.; Gafur, M. A.
ABSTRACT: In this investigation, epoxide (oxirane), a cyclic ether with a three‐atom ring, functional semi‐interpenetrating polymer network (semi‐IPN) hydrogel microspheres composed of temperature‐sensitive poly( N ‐isopropylacrylamide‐ N, N ‐methylene‐bis‐acrylamide) (P(NIPAM‐MBAAm)) and P(NIPAM‐glycidyl methacrylate) (P(NIPAM‐GMA)) are prepared. We called these microspheres as P(NIPAM‐MBAAm)/P(NIPAM‐GMA). The microspheres exhibited temperature‐sensitive volume phase transition at a temperature range of 33–35°C. The chemical bonding of anticancer drugs with the epoxide ring increased the absorption capacity but their release is affected, as the temperature is decreased below the volume phase transition, studied under an in vitro condition suitable for application in the treatment of cancer cells. The epoxide functionality of semi‐IPN hydrogel microspheres is also utilized to isolate inorganic nanoparticles, using Fe3 O4 nanoparticles as an example, simply by blending the hydrogel and magnetic (Fe3 O4 ) dispersions. The presence of strained oxirane ring derived from GMA segment induced high affinity for semi‐IPN hydrogel microspheres toward magnetic Fe3 O4 nanoparticles and eventually reduced the colloidal stability.